2016
DOI: 10.1039/c5ob01844g
|View full text |Cite
|
Sign up to set email alerts
|

Formal synthesis of (−)-podophyllotoxin through the photocyclization of an axially chiral 3,4-bisbenzylidene succinate amide ester – a flow photochemistry approach

Abstract: We have developed a strategy for the stereoselective synthesis of cyclolignans related to podophyllotoxin and its derivatives. The crucial step of the synthesis is the photocyclization of a chiral atropoisomeric 1,2-bisbenzylidenesuccinate amide ester, which can be prepared from suitable aromatic aldehydes, diethyl succinate and l-prolinol. The photocyclization was found to be more efficient when irradiation was performed in a home-built continuous flow photochemical reactor. The in-flow irradiation also allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Finally, (-)-podophyllotoxin and several its analogues were obtained. 19 It was also found that an in-flow procedure was superior compared to the bath type process. This was proven by further synthesis of another cyclolignan (+)-epigalcatin.…”
Section: Atropisomerism In Arylpyridine Derivativesmentioning
confidence: 99%
“…Finally, (-)-podophyllotoxin and several its analogues were obtained. 19 It was also found that an in-flow procedure was superior compared to the bath type process. This was proven by further synthesis of another cyclolignan (+)-epigalcatin.…”
Section: Atropisomerism In Arylpyridine Derivativesmentioning
confidence: 99%
“…56 Homoallylic alcohol 148, constructed using the same asymmetric Evans syn-aldol strategy as in their synthesis of ent-1 (see Scheme 22), 56 was treated with aryl chlorothionoformate 149 to afford thionocarbonate 150. Intramolecular alkene carboxyarylation of 150 with subsequent deprotection completed the total synthesis of (À)-7S-hydroxymatairesinol (117), which was converted to (À)-a-conidendrin (142) upon treatment with TFA.…”
Section: Reviewmentioning
confidence: 99%
“…Only one rotamer was obtained, which was confirmed by NMR analysis. In our previous studies 12,14 we have shown that the use of L-prolinol as a chiral auxiliary provides the P-isomer of the macrocyclic compounds of type 6 (bis-benzylidenesuccinate cyclic amide-ester), which additionally had the cis configuration at C-1 and C-2 chiral centers and the same absolute configuration as in 1. This is a clear advantage of L-prolinol over (-)-ephedrine, which induces the M-configuration 16 of the bis-benzylidenesuccinate cyclic amide-ester and, after cyclization, leads to a trans configuration at C-1 and C-2, and the absolute configuration at C-1 opposite to that found in 1.…”
Section: Synthesis Of Axially Chiral Bis-benzylidenesuccinatementioning
confidence: 99%
“…[7][8][9] Our research group is interested in the stereoselective synthesis of cyclolignans, achieved by photocyclization of chiral bis-benzylidenesuccinates. 10 We found that L-prolinol is an excellent chiral auxiliary 11 and used for the formal synthesis of PPT 12 and the total synthesis of (+)-epigalcatin. 13 We also studied the regioselectivity in the photocyclization of cyclolignan precursors 14 and we used the bis-benzylidenesuccinyl platform as a photolabile protecting group for secondary amines.…”
Section: Introductionmentioning
confidence: 99%